Design Of A Web-Based Inventory Information System Using The Agile Scrum Method Case Study: PT Omega Karyatama Elektronindo - Rieska Rahayu Ayuningsih; Rafly Zulfikar; Dede Sukmawan (International Journal of Health Engineering and Technology, 2026)
Inventory management at PT Omega Karyatama Elektronindo is still carried out manually using written records and spreadsheets, resulting in inaccurate stock data, delayed information, and the absence of a structured procurement workflow. This study aims to design and develop a web-based inventory information system capable of supporting integrated, accurate, and real-time inventory management in accordance with the company's operational needs. The development method used was Agile Scrum, implemented through three sprints: Sprint 1 (Product & Stock Management), Sprint 2 (PR/PO Procurement), and Sprint 3 (Reports & Dashboard). The system was built using the Laravel 12 framework and Filament v5 with a role-based multi-panel architecture that divides access into three panels: Admin, Management, and Supplier. System testing was carried out using the Black Box Testing method on 33 test scenarios across eight functional modules. The results show that the developed web-based inventory information system successfully replaced the manual process and met all the established functional and non-functional requirements, with a testing success rate of 100%.